2007
DOI: 10.1016/j.jacc.2007.07.066
|View full text |Cite
|
Sign up to set email alerts
|

Pre–Drug-Eluting Stent Debulking of Bifurcated Coronary Lesions

Abstract: Directional coronary atherectomy before DES implantation can possibly avoid complex stenting. This strategy may provide a good long-term outcome in patients with bifurcated lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 12 publications
3
38
0
Order By: Relevance
“…The most provocative study to date on the use of DCA for bifurcation lesions was recently published by Tsuchikane et al based on the results of the PERFECT registry [75]. Ninety-nine patients were recruited for this study and all underwent plaque debulking prior to stenting with DES.…”
Section: Directional Coronary Atherectomymentioning
confidence: 99%
“…The most provocative study to date on the use of DCA for bifurcation lesions was recently published by Tsuchikane et al based on the results of the PERFECT registry [75]. Ninety-nine patients were recruited for this study and all underwent plaque debulking prior to stenting with DES.…”
Section: Directional Coronary Atherectomymentioning
confidence: 99%
“…This would allow for pressed. PERFECT study 10) showed that DCA prior to stenting remarkably decreased adverse cardiac events and resulted in good clinical outcomes.…”
Section: Dca In the Futurementioning
confidence: 99%
“…On the other hand, there were some Japanese cardiologists, who strongly desire to revive the DCA device. They reported in 2007 that DCA was useful for limited patients, especially for bifurcated lesions including left main trunk (PERFECT Study) 10) . A new DCA catheter has been developed by NIPRO Corporation (Osaka, Japan) and was approved by the Japan Ministry of Health, Labor and Welfare in December 2014.…”
Section: Mikihiro Kijimamentioning
confidence: 99%
“…However, following the introduction of DES, the role of debulking was restricted due to the dramatic benefit of restenosis reduction. One study suggested a viable role for debulking atherectomy even in the DES era for 99 patients with coronary bifurcations [64] . Of interest, debulking in the main branch and side branch for LMCA stenoses allowed single-stenting in 60 of the 63 LMCA bifurcation stenoses.…”
Section: Debulking Atherectomymentioning
confidence: 99%